Immunoregulatory mechanisms in nonspecific inflammatory bowel disease. - Strickland, R; Jewell, D (1983)
Little is known of either the etiology or the pathogenesis of nonspecific inflammatory bowel disease (IBD). One hypothesis proposes the presence of a disorder of immune regulation as an initiating or perpetuating mechanism of continued bowel wall inflammation in these diseases. This chapter examines the basis for this proposal and reviews recent studies directed toward the demonstration of defective immunoregulatory mechanisms in IBD.